Amazing grace : African American grandmothers as caregivers and conveyors of traditional values - Smith-Ruiz, Dorothy (Praeger, 2004)
Intergenerational African families in which the grandmother is the primary caregiver of grandchildren and great-grandchildren are increasing rapidly in American society. Over the past decade, researchers and policy makers have shown considerable concern over the increases in grandparent-maintained households. This concern has stimulated a proliferation of research on grandparent caregiving on a wide range of issues. Among these are the impact of multiple roles on health, reasons for the rapid increase, problems and needs, social structure and extended family relationships, social support, role.